Evolução do conceito de centro de Saúde no âmbito do novo estatuto do S.N.S. e a criação do nível local de Administração de Saúde. - J C De Sousa; L Campos; M Miranda; M dos A Lima; M G Costa; M M Ornelas; M Galaghar (Acta Médica Portuguesa, 1994)
The authors consider the recently passed about the Portuguese health system reform, namely bills Laws 48/90 and 10/93 (the Bases for Health Law and the National Health Service Act) and they existing some contradictions between the two Laws. In this paper the authors try to adopt point out legislation, mainly the Bases for Health Law from August 24, 1990, as a standard for the conceptualization of a model. One of the proposals in this law, the Health Area, is examined according to the functional contents expressed therein. The authors then probe the concept further, suggesting a local health administration function, at in a Health Area and aimed based a population of about 30,000 inhabitants (from 10 to 50 thousand) and headed by a local Health Administration. The duties and the functional and organizational structure of this body are defined; suggestions for its composition are also advanced. Considering the organizational structure, the authors suggest some services to be supervised by the Local Health Administration: a Public Health Service, a Secretariat and Accounting Service, a Social Service and other. The new concept of Health Center, as the primary care providing unit, is introduced, as is the idea of a Family Medicine Unit, whose functions, definition and scope are proposed.